2020
DOI: 10.1021/acsami.0c02826
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Glutamate Sensing inside the Mouse Brain with Perovskite Nickelate–Nafion Heterostructures

Abstract: Glutamate, one of the main neurotransmitters in the brain, plays a critical role in communication between neurons, neuronal development, and various neurological disorders. Extracellular measurement of neurotransmitters such as glutamate in the brain is important for understanding these processes and developing a new generation of brain–machine interfaces. Here, we demonstrate the use of a perovskite nickelate–Nafion heterostructure as a promising glutamate sensor with a low detection limit of 16 nM and a resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Thus, there is the oxidation of AA to produce DHAA by reducing Ni 3+ to Ni 2+ of NNO NTs (Figure e). A similar behavior has been reported for glucose detection, which has shown that the NdNiO 3 -based biosensors can serve as a sensitive platform for chemical transduction. ,, …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, there is the oxidation of AA to produce DHAA by reducing Ni 3+ to Ni 2+ of NNO NTs (Figure e). A similar behavior has been reported for glucose detection, which has shown that the NdNiO 3 -based biosensors can serve as a sensitive platform for chemical transduction. ,, …”
Section: Resultssupporting
confidence: 74%
“…Also, the electronic properties of these oxides can be tuned by varying their microstructure, strain, and defects . Thus, nickelate’s tunable electronic properties have enabled the exploration of numerous potential applications in electronics, electrocatalysis, and biosensing. , Electrochemical biosensors based on nickelates have been tested only for glucose detection. Sun et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite rare-earth nickelate electrocatalyst is an emerging OER catalyst system. , Previous studies have shown that the electrical properties of nickelate are tightly related to the electronic configuration of a NiO 6 octahedron, which can be effectively manipulated by either natural or artificial stimulus. The partial substitution of an A-site cation and the application of lattice strain can effectively manipulate the Ni–O–Ni bond status, and further, the OER performance. , Herein, we facilely introduce the anionic defect of oxygen vacancies and the cationic defect of a proton (H + ) into the lattice of a single-crystal NdNiO 3 (NNO) thin film by chemical and electrochemical methods, respectively. It is unveiled that the existence of these point defects remarkably suppresses the OER performance, which is rarely observed on most defected perovskite oxides reported before. , By applying a set of characterization studies and first-principles simulations, we discovered that the introduction of point defects suppresses the electron transport across the reaction surface and increases the Ni–O charge-transfer energy which collectively change the rate-determining step (RDS) and enhance the energy barrier of OER.…”
Section: Introductionmentioning
confidence: 99%
“…5) The (1/4, 1/4, 1/4) antiferromagnetic order breaks down after some critical doping [28]. Many exciting applications have been proposed and realized in these interstitially-doped nickelates, e.g., electronic devices (phase-change transistor) [19,[29][30][31], fuel cells [22], bio-electronic interfaces [32,33], electric field sensor [21], as well as artificial cognitive systems [28,34,35].…”
Section: Interstitial Ion Dopingmentioning
confidence: 99%